Health services for reproductive tract infections among female migrant workers in industrial zones in Ha Noi, Viet Nam: an in-depth assessment - Kim, Le Anh Thi (BioMed Central, 2012)
BACKGROUND: Rural-to-urban migration involves a high proportion of females because job opportunities for female migrants have increased in urban industrial areas. Those who migrate may be healthier than those staying in the village and they may benefit from better health care services at destination, but the 'healthy' effect can be reversed at destination due to migration-related health risk factors. The study aimed to explore the need for health care services for reproductive tract infections (RTIs) among female migrants working in the Sai Dong industrial zone as well as their services utilization. METHODS: The cross sectional study employed a mixed method approach. A cohort of 300 female migrants was interviewed to collect quantitative data. Two focus groups and 20 in-depth interviews were conducted to collect qualitative data. We have used frequency and cross-tabulation techniques to analyze the quantitative data and the qualitative data was used to triangulate and to provide more in-depth information. RESULTS: The needs for health care services for RTI were high as 25% of participants had RTI syndromes. Only 21.6% of female migrants having RTI syndromes ever seek helps for health care services. Barriers preventing migrants to access services were traditional values, long working hours, lack of information, and high cost of services. Employers had limited interests in reproductive health of female migrants, and there was ineffective collaboration between the local health system and enterprises. These barriers were partly caused by lack of health promotion programs suitable for migrants. Most respondents needed more information on RTIs and preferred to receive these from their employers since they commonly work shifts - and spend most of their day time at work. CONCLUSION: While RTIs are a common health problem among female migrant workers in industrial zones, female migrants had many obstacles in accessing RTI care services. The findings from this study will help to design intervention models for RTI among this vulnerable group such as communication for behavioural impact of RTI health care, fostered collaboration between local health care services and employer enterprises, and on-site service (e.g. local or enterprise health clinics) strengthening.